2015
DOI: 10.1586/14737175.2015.1081815
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes of subthalamic nucleus deep brain stimulation in Parkinson’s disease

Abstract: The subthalamic nucleus (STN) has been a major target of deep brain stimulation (DBS) for Parkinson's disease (PD) over the past 20 years. The benefits of DBS of the STN include: decreased motor fluctuations and bradykinesia, tremor reduction and a reduction in dopaminergic drug requirements and dyskinesias. Despite these overall positive effects, the outcomes of STN DBS can be variable, contributing to the debate over the best DBS target for PD. Here, the authors review the current practice of STN DBS and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 61 publications
1
29
0
2
Order By: Relevance
“…Measures of motor disability (using Unified Parkinson's Disease Rating Scale III) were improved by up to 73% when combined with medication; and performance of activities of daily living were improved by up to 60% compared to pre‐surgical levels (Schüpbach et al .). DBS is recognised as a surgical intervention that requires ongoing, specialised management to reduce the temporary and permanent side effects or complications of the treatment, and optimise symptom outcomes (Bari, Fasano, Munhoz & Lozano, ). It is acknowledged that along with the usual risks of neurosurgery, there are a range of complications that are often transient or modifiable, occurring around the time of surgery or when there are changes to stimulation programming or medication.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of motor disability (using Unified Parkinson's Disease Rating Scale III) were improved by up to 73% when combined with medication; and performance of activities of daily living were improved by up to 60% compared to pre‐surgical levels (Schüpbach et al .). DBS is recognised as a surgical intervention that requires ongoing, specialised management to reduce the temporary and permanent side effects or complications of the treatment, and optimise symptom outcomes (Bari, Fasano, Munhoz & Lozano, ). It is acknowledged that along with the usual risks of neurosurgery, there are a range of complications that are often transient or modifiable, occurring around the time of surgery or when there are changes to stimulation programming or medication.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, the probe is placed in the white matter tract leading to the hippocampus called the fornix [96,97], or the nucleus basalis of Meynert [98] instead of where it is placed in PD patients for recovery of motor function (e.g. the subthalamic nucleus) [99,100]. It has been demonstrated that stimulation of these areas can improve cognitive deficits via enhancement of hippocampal function in many rodent neurodegenerative (e.g.…”
Section: Non-invasive Deep Brain Stimulation-deep Brain Stimulation (mentioning
confidence: 99%
“…The existence of depressive symptoms is not per se a contraindication to DBS surgery. However, ongoing severe depression, psychotic symptoms, and suicidal ideation should be considered absolute contraindications as they might worsen and increase suicidal risk, particularly in the first year after surgery (5052). Less evidence is available regarding severe depressive patients who were eventually stabilized by psychotherapy and medication, months or years prior to undergoing DBS: a trend toward a slightly worse motor and mood outcome has been described, but this certainly does not constitute an absolute contraindication to surgery (53).…”
Section: Management Of Depression In the Preoperative And Postoperatimentioning
confidence: 99%